Plyometric training improves sprinting, jumping and throwing capacities of high level female volleyball players better than skill-based conditioning - Gjinovci, B.; Idrizovic, K.; Uljevic, O.; Sekulic, D. (Journal of Sports Science & Medicine, 2017)
There is an evident lack of studies on the effectiveness of plyometric- and skill-based-conditioning in volleyball. This study aimed to evaluate effects of 12-week plyometric- and volleyball-skill-based training on specific conditioning abilities in female volleyball players. The sample included 41 high-level female volleyball players (21.8 ± 2.1 years of age; 1.76 ± 0.06 cm; 60.8 ± 7.0 kg), who participated in plyometric- (n = 21), or skill-based-conditioning-program (n = 20). Both programs were performed twice per week. Participants were tested on body-height, body-mass (BM), countermovement jump (CMJ), standing broad jump (SBJ), medicine ball throw, (MBT) and 20-m sprint (S20M). All tests were assessed at the study baseline (pre-) and at the end of the 12-week programs (post-testing). Two-way ANOVA for repeated measurements showed significant (p<0.05) "Group x Time" effects for all variables but body-height. Plyometric group significantly reduced body-mass (trivial effect size [ES] differences; 1% average pre- to post-measurement changes), and improved their performance in S20M (moderate ES; 8%), MBT (very large ES; 25%), CMJ (large ES; 27%), and SBJ (moderate ES; 8%). Players involved in skill-based-conditioning significantly improved CMJ (large ES; 18%), SBJ (small ES; 3%), and MBT (large ES; 9%). The changes which occurred between pre- and post-testing were more inter-correlated in plyometric-group. Although both training-modalities induced positive changes in jumping- and throwing-capacities, plyometric-training is found to be more effective than skill-based conditioning in improvement of conditioning capacities of female senior volleyball players. Future studies should evaluate differential program effects in less experienced and younger players